Influence of the Climate Policy of the European Union on the Competitiveness of Pollution-generating Sectors of the Polish Economy in the Context of Sustainable Development; Wpływ polityki klimatycznej Unii Europejskiej na konkurencyjnosćṕolutogennych sektoroẃ polskiej gospodarki w konteksćie zroẃnowazȯnego rozwoju - Małgorzata Burchard-Dziubinśka (Comparative Economic Research. Central and Eastern Europe, 2011)
The text analyses the influence of the EU climate policy on the competitiveness pollution-generating of sectors of the Polish economy. Study of literature and the results of the questionnaire survey, carried out in 2008 in enterprises located in Poland and representing the steel, glass, aluminium and cement industries became a basis for formulating conclusions concerning the consequences of the climate policy already implemented and planned after 2012. The EU climate policy, particularly the common system of emission allowances trade, makes the enterprises face new developmental barriers. The expected increase in production costs will not only slow down the production dynamics, but may also entail lowering the competitiveness of Polish companies compared to companies from outside the EU, to which the greenhouse gasses emission limits do not apply. Adverse consequences for employment and for regional development should also be considered indisputable. If that was accompanied by an emission leakage outside the EU, achieving the global purposes of the climate policy would also become questionable. The businesses surveyed represent industries which are pollution generators by their nature and even ecologically-oriented technological progress is incapable of ensuring considerable emission reductions without general switching of the economy to renewable energy sources. – – W teksćie przedmiotem analizy jest wpływ polityki klimatycznej UE na konkurencyjnosćṕolutogennych sektoroẃ polskiej gospodarki. Analiza literatury i wyniki badanṕrzeprowadzonych w 2008 r. w zlokalizowanych na terenie Polski przedsiebiorstwach reprezentujacych hutnictwo zėlaza, szkła, aluminium oraz przemysł cementowy stanowia podstawe do sformułowania wnioskoẃ dotyczacych konsekwencji juzṗrowadzonej i planowanej po 2012 r. polityki klimatycznej UE. Polityka klimatyczna UE, zwłaszcza wspoĺnotowy system handlu pozwoleniami do emisji, stwarzaja dla przedsiebiorstw nowe bariery rozwoju. Oczekiwany wzrost kosztoẃ produkcji, mozė nie tylko spowolnicd́ynamike produkcji, ale takzė obnizẏcḱonkurencyjnosćṕolskich przedsiebiorstw w stosunku do przedsiebiorstw spoza UE, ktoŕe nie musza dostosowywacśie do redukcji emisji gazoẃ cieplarnianych. Pod uwage nalezẏ bract́akzė konsekwencje dla zatrudnienia i rozwoju regionalnego. Jesĺi wystapiłby roẃniezẇyciek emisji poza UE osiagniecie globalnych celoẃ polityki klimatycznej stałoby sie bardzo watpliwe. Branzė uwzglednione w badaniu sa ze swej natury polutogenne i nawet proekologiczne przemiany technologiczne nie sa w stanie zapewnicŕedukcji emisji bez generalnego przestawienia sie gospodarki na odnawialne zŕod́ła energii.
Keywords: 330